PENGARUH PENGGUNAAN MEDIA SOFTWARE SIMULASI ELECTRICAL CONTROLTECHNIQUES SIMULATOR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK PADA KOMPETENSI DASAR PENGASUTAN MOTOR LISTRIK - Dinan Roy Sandi Siburian; Arwadi Sinuraya (Universitas Negeri Medan, 2021)
Abstract This study aims to find out if the use of Electrical Control Techniques Simulator (EKTS) Simulation Software as a learning medium in electrical motor installation subjects can improve students' learning outcomes in Grade XI TITL At SMK Negeri 1 Percut Sei Tuan.. Abstract must reflect the overall substance of the article content and be able to help readers determine its relevance to their interests and decide whether to read the document in its entirety. The research was conducted at SMKN 1 Percut Sei Tuan which is located at Jalan Kolam No 3 Kenangan Baru, Kec Percut Seituan, Deli Serdang Regency and the research time will be conducted in the odd semester of the 2019-2020 School Year. The object of this research is the learning media in the form of software electrical control techniquessimulator subjects electrical motor installation. The subjects in this study were students of grade XI Electrical Installation Engineering at SMKN 1Percut Sei Tuan, with a sample of Class XI TITL 2 research. The results showed that in general, the learning media of Electrical Control Techniques Simulator simulation software has a significant influence on students' learning outcomes. The results of learning the installation of electric motors students who are taught using the learning media simulation software Electrical Control Techniques Simulator can be higher because through this learning media students can more easily understand a series of installations of motor linking through the animation of the series of electric motors displayed by the simulation software media Electrical Control Techniques Simulator Where the average learning outcome of students who are taught with the Learning Media simulation software Electrical Control Techniques Simulator obtained a score of 8.01 with the highest score being 9.0 and the lowest score being 7.0 compared to students taught with learning media The Whiteboard obtained an average score of 6.544 with the highest score being 7.5 and the lowest score being 5.0. Key Words: Electrical control techniques, motor instalationAbstrakPenelitian ini bertujuan untuk mengetahui apakah penggunaan Software Simulasi Electrical Control Techniques Simulator (EKTS) sebagai media pembelajaran pada mata pelajaran instalsi motor listrik dapat meningkatkan hasil belajar siswa di Kelas XI TITL Di SMK Negeri 1 Percut Sei Tuan. Penelitian dilaksanakan di SMKN 1 Percut Sei Tuan yang beralamat di Jalan Kolam No 3 Kenangan Baru, Kec. Percut Sei Tuan, Kab. Deli Serdang dan waktu penelitian dilaksanakan pada semester ganjil T.A. 2019-2020. Objek penelitian ini adalah media pembelajaran berupa Software electrical control techniquessimulator mata pelajaran instalasi motor listrik. Subjek dalam penelitian ini adalah siswa kelas XI Teknik Instalasi Tenaga Listrik di SMKN 1 Percut Sei Tuan, dengan sampel penelitian Kelas XI TITL 2. Hasil penelitian menunjukkan bahwa secara umum Media pembelajaran software simulasi Electrical Control Techniques Simulator memberikan pengaruh yang signifikan terhadap hasil belajar siswa. Hasil belajar instalasi motor listrik siswa yang diajar dengan menggunakan Media pembelajaran software simulasi Electrical Control Techniques Simulator dapat lebih tinggi karena melalui Media pembelajaran ini siswa dapat lebih mudah untuk memahami sebuah rangkaian instalasi pengasutan motor melalui animasi rangkaian motor listrik yang ditampilkan oleh media software simulasi Electrical Control Techniques Simulator Dimana rata-rata hasil belajar siswa yang diajar dengan Media pembelajaran software simulasi Electrical Control Techniques Simulator memperoleh nilai 8,01 dengan nilai tertinggi adalah 9,0 dan nilai terendah adalah 7,0 dibandingkan dengan siswa yang diajar dengan media pembelajaran Papan Tulis memperoleh nilai rata-rata 6,544 dengan nilai tertinggi adalah 7,5 dan nilai terendah adalah 5,0.Kata Kunci: Electrical control techniques, instalasi motor